Hydroxyapatite Production from Cuttlebone as Bone Scaffold Material Preparations - Krisman Umbu Henggu; Bustami Ibrahim; Pipih Suptijah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
The increasing production of cuttlefish has been associated with the increasing of by-product waste particularly cuttlebone. Cuttlebone is known to contain an inorganic element in form of calcium carbonate(CaCO3) which can be utilized as a source of calcium oxide (CaO) for hydroxyapatite synthesis. This study was aimed to determine the physicochemical characteristics of the cuttlebone and the optimum calcination temperature for CaO extraction and hydroxyapatite synthesis. This study was divided into three steps. Firstly, analysis of the cuttlebone physicochemical properties; secondly, extraction and characterization of the CaO with different calcination temperature (500°C, 600°C, 700°C for 6 hours); and thirdly, hydroxyapatite synthesis using a combination of hydrothermal method at 200°C 6 hours and different calcination treatments (800°C, 900°C, 1,000°C for 1 hour). The results showed that the cuttlebone contained moisture 3.54±0.11%,lipid 0.32±0.19%, protein 4.78±0.23%, carbohydrate 5.29±0.02%, and ash 89.61±0.26. The main element of the ash was CaCO3 aragonite characterized by the high absorption at wavelengths of 1,795; 1,507;1,083; 871; 713 and 700 cm-1. The calcination treatment of 700°C produced the highest amount of CaO. The hydroxyapatite produced with a combination of hydrothermal and calcination temperature 1,000°Chad calcium phosphate ratio (Ca/P) 1.66, crystalline level 90.10%, amorphous level 9.90% and particles morphology of rod-shaped.